# Chemistry

What is the enthalpy change for the first reaction?

Fe2O3(s) → 2Fe(s) + 3/2O2(g) ΔH =

4Fe(s) + 3O2(g) → 2Fe2O3 (s) ΔH = -1,652 kJ

I think I'm supposed to rearrange the equation and double everything but enthalpy isn't my strong suit

1. 👍
2. 👎
3. 👁
1. You can do this two ways.
The first is to take equation 1 and use
dHrxn = (n*dHf products) - (n*dHf reactants). When you look these up you will find dH Fe is zero and dH O2 is zero so it is a simple calculation and you don't have anything else to do.
OR
you can recognize that equation 1 is the reverse of the heat of formation which is written as equation 2 EXCEPT that heat of formation actually is
2Fe + 3/2O2 ==> Fe2O3 so what is written as equation 2 is twice heat formation. Take half of that to get -851 kJ and change the sign to make it +851 kJ for the reverse and that will be kJ for equation 1.

1. 👍
2. 👎
2. Consider the reaction:

2Al(s) + Fe2O3(s) → Al2O3(s) + 2Fe(s)

The ΔHf for Fe2O3(s) = -824.3 kJ/mole. The ΔHf for Al2O3(s) = -1675.7 kJ/mole.

Finish the equation.

ΔHrxn = [(1)( kJ/mole) + (2)( kJ/mole)] - [(1)( kJ/mole) + (2) ( kJ/mole)]

1. 👍
2. 👎
3. It's actually more simple than that.
Divide the entire equation by two in order to make the Fe2O3 be equal to one mol of the substance.
"(2Fe(s) + 3/2 O2(g) → Fe2O3 (s) ΔH = -826 kJ)"

This will also divide the enthalpy by 2 (-1652/2 = -826). Then, use the molar mass of Fe, times the mol-to-mol ratio of Fe and Fe2O3, times conversion factor provided by the enthalpy of the reaction (-826 KJ/1 mol)

11.2g Fe (1 mol/55.85)(1 Fe2O3 mol/ 2 Fe mol)(-826 KJ/1 mol)
11.2g (1/55.85)(1/2)(-826/1) = -82.8KJ

Hope it helps!

1. 👍
2. 👎

## Similar Questions

1. ### chemistry

2C2H2(g) + 5O2(g)→4CO2(g) + 2H2O(g) a. Determine the enthalpy change for the reaction. ΔH = (4(-393.5)+ 2(-241.8)) – (2(227) + 5(0)) The enthalpy change is -2511.6. b. Determine the entropy change for the reaction. ΔS =

2. ### Chemistry

Which element is oxidized in this reaction? Fe2O3+ 3CO-(arrow)2Fe+3CO2

3. ### Chemistry

Enthalpy Change Given the following reactions: S(s) + O2(g) → SO2(g) ΔH = -297 kJ/mol SO2(g) + ½ O2(g) → SO3(g) ΔH = -141 kJ/mol Calculate the ΔH for the reaction: S(s) + 3/2O2(g) → SO3(g)

4. ### Chemistry due soon

If the following reaction: NO(g) + 1/2O2(g) NO2(g) has the following enthalpy change: H° = -56 kJ/mol What is the enthalpy of the decomposition reaction of 2 moles of NO2? A. 112 kJ B. 56 kJ C. -56 kJ D. -112 kJ i think the

1. ### Chemistry

How many grams of CO are needed to react with an excess of Fe2O3 to produce 209.7gFe? Fe2O3(s) + 3CO(g) => 3CO2(g) + 2Fe(s)

2. ### Honors Chemistry

Equation: Fe2O3 + 2Al ---> 2Fe + Al2O3. How many grams of Fe2O3 react with excess Al to make 475g Fe? Can you show me step by step how to do it? My book says the answer is 679g Fe2O3.

3. ### Chemistry

Calculate the enthalpy change, ∆H in kJ, for the reaction H2O(s) → H2(g) + 1/2O2(g) Use the following: A. –291.9 kJ B. +291.9 kJ C. –279.9 k D. +279.9 kJ D??

4. ### chemistry

Calculate enthalpy change of reaction for the combustion of gaseous ethanol. C2H5OH + 3O2 >> CO2 + 3H2O. Using standard molar enthalpies of formation. C2H5OH -235.3 ( it's negative sign) CO2 -393.5 H2O -241.8 (1) Calculate the

1. ### Chemistry

Find the enthalpy for : 4Fe + 3O2 = 2Fe2O3 I got the following informations: Fe + 3H2O = Fe(OH)3 + 3/2H2 - Enthalpy is 160.9 kj H2 + 1/2O2 = H2O - Enthalpy is -285.8 kj Fe2O3 + 3H2O = 2Fe(OH)3 - Enthalpy is 288.6 I try using Hess

2. ### Chemistry

Calculate the enthalpy change (delta H) in kJ for the following reaction. 2Al(s) + Fe2O3 (s) ==> 2 Fe(s) + Al2O3(s) use enthalpy changes for the combustion of aluminum and iron. 2Al(s) + 3/2 O2(g) ==> Al2O3(s) Delta H: -1669.8 kJ

3. ### Last Question Plz helppp:((im soo sleepy!!:(

1)The reaction between solid sodium and iron(III) oxide, Fe2O3(s), is one in a series of reactions that occurs when an automobile air bag inflates. 6Na(s) + Fe2O3(s) -> 3Na2o(s) + 2Fe(s) If 100.0 g of iron(III) oxide are used in

4. ### Chemistry

Calculate the enthalpy change for: C2H4(g) + H2 --> C2H6(g) delta Hrxn: H2(g) + 1/2O2 --> H2O (l) C2H4(g) + 3O2 --> 2H20(l) + 2CO2(g) C2H6(g) + 7/2O2(g) --> 3H20(l) + 2CO2(g) I know I have to flip the third reaction but I don't